Cooperative work for the development of the logic mathematical skills in the preschool students - Diaz Tapia, Lirys; de la Cruz, Nancy; Viteri Valle, Victor; Vistin Chacan, Manuel (Revista Universidad de Guayaquil, 2018)
Collaborative job, also known as peer technique (PT), offers an alternative for the development of mathematical logic skills in preschool students. There are factors such as collaboration, communication and especially the face-to-face interaction of the students, which together with the teacher's performance, interact to achieve the best performance of the students. The intention is to improve the quality of learning in preschool students, and at the same time, combine it with the competencies and skills of the teacher, to strengthen the development of each and every one of the abilities of students, using mathematical logic.The research is qualitative and descriptive. Hermeneutics and phenomenology help the interpretation of the different authors to complement the study. The results of the research are focused on cooperative work, based on a learning methodology, developing new strategies for its best application, and at the same time, improving the skills of mathematical logic. With the application of the techniques by pairs, satisfactory results will be obtained, to develop the cognitive processes of the preschool students. This methodology includes the family environment, to obtain the entire process.
Keywords: Cooperative learning; collaborative work components of collaborative job; peer techniques; peer job